Intervention proposal to standardize patient restraint in the intensive care unit of a public hospital: An experience report (Research, Society and Development, 2024)
The aim of this report is to narrate the experience of a nursing resident in conducting an intervention project to standardize the process of restraining patients in an Intensive Care Unit (ICU). This descriptive, qualitative study adopts the experience report approach and covers the development of an intervention proposal from March to December 2023, based on the PDCA methodology. Data collection involved brainstorming with the participation of the multi-professional team, answering the question: "What are the obstacles to systematizing patient restraint in the ICU?" The answers, analyzed using project management tools such as the Ishikawa Diagram, GUT Matrix and 5W2H Matrix, formed the basis for the results presented in this report. The results include the identification, grouping and prioritization of the causes of the problem, culminating in the proposed intervention with action plans to address the eleven root causes that prevent the systematization of restraint in the ICU. Challenges were foreseen during implementation, such as employee resistance, limited financial resources and the possible discontinuation of the project over time. In conclusion, the successful construction of this proposal highlights the practical applicability of management tools and their substantial contributions to problem-solving. The resident acquired technical and behavioral skills, demonstrated leadership ability and developed an in-depth understanding of these tools throughout the experience.